(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This study examines the preconditions for the formation of the museum network in Karakalpakstan, a region in northwestern Uzbekistan with a rich multicultural heritage. The research identifies four primary factors that shaped museum development: historical-cultural, scientific-research, socio-political, and administrative-legal prerequisites. The historical-cultural foundation stems from Karakalpakstan’s position as a crossroads of ancient civilizations, including the Khorezm states, Achaemenid Empire, and various Turkic and Mongol polities, resulting in abundant archaeological sites such as Toprak-Kala, Ayaz-Kala, and the Mizdakhkan necropolis. The scientific-research impetus emerged from the groundbreaking work of the Khorezm Archaeological and Ethnographic Expedition (1937-1990), led by S.P. Tolstov, which systematically documented archaeological and ethnographic materials using innovative methods including aerial photography. Socio-political transformations in the 20th century, particularly the administrative reorganizations of 1924-1936 and nation-building processes within the Soviet framework, created institutional support for cultural preservation. The establishment of the Karakalpak branch of the Academy of Sciences in 1959 further strengthened the scientific foundation for museum activities. The study demonstrates that the museum network in Karakalpakstan developed through the convergence of these interrelated factors, serving dual purposes of preserving cultural heritage and facilitating cultural modernization. This research contributes to understanding regional museum development patterns in Central Asia and highlights the role of museums in safeguarding both tangible and intangible cultural heritage in historically complex territories.